PENGARUH UKURAN PERUSAHAAN, LEVERAGES, SISTEM PENGENDALIAN INTERNAL, DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY DENGAN AUDIT TENURE SEBAGAI VARIABEL MODERASI - Fadjar Harimurti, Putri Intan Prastiwi, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
The purpose of this research is to analyze the effect of company size, leverages, internal control system, auditor’s reputationon audit delay with audit tenure as moderation variable. This is study empirical on foods and beverages campanies listed in Indonesian Stock Exchange (IDX) period 2013 - 2016. The data source uses secondary data. Study population is 16 companies with analyze of financial report and independent auditor’s report period 2013 - 2016 accessed wih IDX websites www.idx.co.id. Sampling technique is purposive sampling with sample of researh is 10 companies. Data collection techniques use documentation metohd and literature review. Data analysis used multiple linear regression and absolute difference test. The results showed that company size has a not significant on audit delay, leverages has a not significant on audit delay, internal control system has a not significant, auditor’s reputation has a negatif significant on audit delay, audit tenure does moderate the auditor’s reputation effect on audit delay.Keywords: company size, leverages, internal control system, auditor’s reputation, audit tenure, audit delay